A multiproxy study distinguishes environmental change from diagenetic alteration in the recent sedimentary record of the inner Cadiz Bay (SW Spain). (September 2016) - Jiménez-Arias, Juan L; Mata, M Pilar; Corzo, Alfonso; Poulton, Simon W; März, Christian; Sánchez-Bellón, Angel; Martínez-López, Javier; Casas-Ruiz, Melquiades; García-Robledo, Emilio; Bohórquez, Julio; Papaspyrou, Sokratis
In this study, we reconstruct the recent environmental evolution of the inner Cadiz Bay using sedimentary records reaching back as far as AD 1700. We report lithological descriptions of the sediments and extensive mineralogical and geochemical analyses. An extraction technique that identifies different Fe phases provides an assessment of diagenetic alteration, which allows an estimation of the original organic matter inputs to the inner Cadiz Bay. Downcore variations in Corg/N ratios, δ 13 Corg and δ 15 N are related to changes in organic matter sources and the trophic state of the water column. The downcore records of selected trace metals (e.g. Pb, Zn and Cu) are interpreted to reflect changes in heavy metal pollution in the bay, while records of other elements (e.g. Mn and P) are likely overprinted by diagenetic alteration. Major environmental shifts took place during the 20th century, when the population around Cadiz Bay increased exponentially. Increases in sediment accumulation rates, organic matter inputs and heavy metal contents, in parallel with increases in δ 13 Corg and δ 15 N over this period, are interpreted as direct effects of the increasing anthropogenic influence in the area. The results of this study suggest that multiproxy approaches and detailed consideration of diagenetic overprinting are required to reconstruct past environmental conditions from coastal sediments.